1993
DOI: 10.1093/cvr/27.12.2130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endothelins on collagen turnover in cardiac fibroblasts

Abstract: ET-1 and ET-3 increased the synthesis of type I and III collagens, whereas ET-1, but not ET-3, reduced collagenase activity. The effects of endothelins on collagen synthesis in cardiac fibroblasts seem to be mediated through ETA and ETB receptors, whereas their effects on collagenase seem to be mediated by ETA receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
9

Year Published

1994
1994
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(137 citation statements)
references
References 0 publications
5
123
0
9
Order By: Relevance
“…26 The early release of TGF-␤1 from necrotic myocytes and macrophages is also important in the phenotypic transformation of interstitial fibroblasts to myofibroblasts, which elaborate receptors to Ang II, TGF-␤1, and ET-1. 26,28 Myofibroblasts express genes encoding for procollagen types 1 and 3, generate Ang I and II and receptors for Ang II and TGF-␤1 and ET-1; this enables the autoregulation of collagen turnover. 4,26 Synthesis of collagen types 1 and 3 by myofibroblasts is modulated by several factors, including Ang II-related mechanical deformation, fibroblast growth factor, platelet-derived growth factor, ANP, and bradykininmediated prostaglandin E2 and nitric oxide release.…”
Section: Triggers For Tissue Repairmentioning
confidence: 99%
“…26 The early release of TGF-␤1 from necrotic myocytes and macrophages is also important in the phenotypic transformation of interstitial fibroblasts to myofibroblasts, which elaborate receptors to Ang II, TGF-␤1, and ET-1. 26,28 Myofibroblasts express genes encoding for procollagen types 1 and 3, generate Ang I and II and receptors for Ang II and TGF-␤1 and ET-1; this enables the autoregulation of collagen turnover. 4,26 Synthesis of collagen types 1 and 3 by myofibroblasts is modulated by several factors, including Ang II-related mechanical deformation, fibroblast growth factor, platelet-derived growth factor, ANP, and bradykininmediated prostaglandin E2 and nitric oxide release.…”
Section: Triggers For Tissue Repairmentioning
confidence: 99%
“…3 H]Proline incorporation by cardiac fibroblasts was measured according to modified methods of Guarda et al (26). Briefly, cells were transferred to 12-well plates then were serum starved in 0% FBS for 24 h. Proline incorporation was then assayed by adding 1 Ci/well of [ 3 H]proline (PerkinElmer Life Sciences) along with, where indicated, drugs of interest and 2.5% FBS for 24 h. Cells were removed by trypsinization and protein precipitated overnight with 20% trichloroacetic acid.…”
Section: Assay Of Collagenase-sensitive [ 3 H]proline Incorporation-[mentioning
confidence: 99%
“…Guarda et al 79 have found that endothelin-1 (ET-1) and ET-3 each increase cardiac fibroblast collagen synthesis and the synthesis of its types I and III phenotype in a concentration-dependent manner. Both ET A and ET B receptors were involved in this response.…”
Section: Endothelinsmentioning
confidence: 99%